Natural mineral-derived Fe/Mn-BC as efficient peroxydisulfate activator for 2, 4-dichlorophenol removal from wastewater: Performance and sustainable catalytic mechanism. (1st June 2023) - Zhang, Ke; Huang, Dongli; Zhang, Ying; El Houda Bouroubi, Nour; Chen, Pan; Ganbold, Naranchimeg; He, Peng; Liu, Junwu; Fang, Yingchun; Gan, Min; Zhu, Jianyu; Yang, Baojun
Abstract: Iron and manganese oxides/biochar composite materials (Fe/Mn-BC) are promising catalysts in the field of advanced oxidation. High purity chemical reagents are popular precursors for preparing Fe/Mn-BC, while the potential of low-cost natural minerals as precursors has been neglected. In this study, high-efficiency Fe/Mn-BC was synthesized by one-step pyrolysis method using hematite, phosphoromanganese, and bagasse. The synthesized Fe/Mn-BC removed 83.7% 2, 4-dichlorophenol (2, 4-DCP) within 30 min, about 8.8 and 10.6 times better than biochar (BC) and Fe/Mn complex, respectively. The removal of 2, 4-DCP in the Fe/Mn-BC + peroxydisulfate (PDS) system was influenced by catalyst dosage, PDS concentration, initial pH, organic acids, and chromium. Sulfate radical (SO4 - ) and hydroxyl radicals (OH) generated by Fe/Mn-BC-activated PDS have similar contribution to the degradation of 2, 4-DCP. A possible removal mechanism of 2, 4-DCP in the Fe/Mn-BC + PDS system was proposed based on Electron Spin Resonance spectroscopy, free radical quenching experiments, X-ray photoelectron spectroscopy, X-ray diffraction, and electrochemical measurement. Fe 0 and Fe(II) in Fe/Mn-BC play significant role in catalytic degradation of 2, 4-DCP at the early stage of the reaction (within 0–5 min). Then, the interaction between Mn and BC or structural Mn and structural Fe gradually became dominant in the later stage. Similarly, the electron transfer promoted by biochar also played an important role in this catalysis. This discovery provided a new strategy for developing iron and manganese oxides/biochar composite materials to activate PDS for the elimination of refractory organic pollutants. Graphical abstract: Image 1 Highlights: Fe/Mn@BC was fabricated by a one-step pyrolysis method using natural minerals. The Fe/Mn@BC-PDS system had efficient and sustained 2, 4-DCP degradation capacity. Fe(0) and Fe(II) in Fe/Mn@BC played key roles at the early stage of the reaction. The interaction between Mn and Fe enhanced the catalysis in later stage reaction. The electron transfer promoted by biochar contributed to 2, 4-DCP degradation.